Predictors of patients with advanced pancreatic cancer undergoing conversion surgery via chemoimmunotherapy with a multifunctional Wilms’ tumor 1 (WT1) peptide cocktail-pulsed dendritic cell vaccine - Nobuhiro Sato; Shigetaka Shimodaira; Masayuki Saruta; Yoko Shimizu; Shigeo Koido; Junichi Taguchi; Masamori Shimabuku; Tuuse Bito; Zensho Ito; Kan Uchiyama; Toshifumi Ohkusa; Haruo Sugiyama; et al. (Journal for ImmunoTherapy of Cancer, 2025)
Background A chemoimmunotherapy regimen consisting of a novel Wilms’ tumor 1 (WT1) peptide-pulsed dendritic cell (WT1-DC) vaccine and multiagent chemotherapy was observed to modulate the tumor microenvironment (TME) to an immunostimulatory state, resulting in conversion surgery in seven out of nine patients with unresectable pancreatic ductal adenocarcinoma (UR-PDAC).Methods Understanding WT1-specific immunity and the tumor mutational burden is important for predicting the efficacy of WT1-targeted chemoimmunotherapy. Therefore, the memory CD8+T cell subpopulations in WT1-specific cytotoxic T lymphocytes (WT1-CTLs), titers of antibodies against the WT1 epitopes, infiltration of CD103+tissue-resident memory T cells and CD20+cells in the pancreatic TME, gene mutations in plasma circulating tumor DNA (ctDNA) obtained via liquid biopsy, and PDAC cell characteristics were evaluated.Results Prior to treatment, patients with a relatively low number of WT1-specific CD8+naive T (Tn) cells, high levels of WT1-specific IgM antibodies, no mutations in any key genes (KRAS and TP53) in plasma ctDNA that were different in each patient (ie, neoantigens), and low levels of programmed death-ligand 1 expression in PDAC cells presented a markedly superior prognosis compared with patients with alternative patterns. Administration of WT1-targeted chemoimmunotherapy resulted in a significant increase in the proportion of circulating WT1-specific CD8+central memory T (Tcm) cells in super-responders (SRs: progression-free survival (PFS)>median) compared with non-super-responders (NSRs: PFS≤median). Moreover, the ratio of Tcm to terminally differentiated effector memory T cells in WT1-CTLs was greater in SRs than in NSRs after 15 vaccinations. In patients harboring at least one mutated ctDNA, the frequency of each ctDNA mutant allele significantly decreased after WT1-targeted chemoimmunotherapy. In addition, one SR showed remarkably high infiltration of CD103+ or CD20+ cells in the pancreatic TME; however, there was no association between these cell densities and clinical outcomes.Conclusions In patients with UR-PDAC who exhibited spontaneous activation of WT1-specific cellular and humoral immunity prior to treatment, endogenous WT1-specific CD8+Tn cells were engineered into WT1-specific memory CD8+cells via WT1-targeted chemoimmunotherapy, resulting in superior therapeutic effects. WT1-targeted chemoimmunotherapy also induced neoantigen-specific immune responses via epitope spreading, leading to the elimination of neoantigen-expressing PDAC cells and favorable clinical outcomes.Trial registration number jRCTc030190195.